Understanding COVID-19: From Dysregulated Immunity to Vaccination Status Quo - Escobedo, Ruby A.; Singh, Dhiraj K.; Kaushal, Deepak (Frontiers in Immunology, 2021)
The development of vaccines against infectious diseases has helped us battle the greatest threat to public health. With the emergence of novel viruses, targeted immunotherapeutics ranging from informed vaccine development to personalized medicine may be the very thing that separates us between life and death. Late in 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the etiological agent of coronavirus disease 2019 (COVID-19), made a remarkable entrance to human civilization, being one of many to cross the species barrier. This review discusses the important aspects of COVID-19, providing a brief overview of our current understanding of dysregulated immune responses developed using various experimental models, a brief outline of experimental models of COVID-19 and more importantly, the rapid development of vaccines against COVID-19.